The Relationship Between The Level of Knowledge, and Motivation of Women of Childbearing Age in Visual Inspection with Acetic Acid (VIA) Examination in The Working Area of The Rawamerta Health Center - Nining Sari Asih; Nofa Anggraini (Sean Institute, 2023)
Mortality from cervical cancer in Indonesia is getting higher because more than 70% of cases that come to the hospital are at an advanced stage. This phenomenon is due to the low coverage of early detection of cervical cancer including PAP smear tests and visual inspection with acetic acid (VIA). The purpose of this study was to determine the relationship between the level of knowledge, and motivation of women of childbearing age in the examination of visual inspection with acetic acid (VIA) in the working area of the rawamerta health center. This study is an observational analytic correlation with a cross-sectional research design. The research location was at the Rawamerta Health Center which is the working area of the Rawamerta Health Center, Karawang Regency. The sample in this study was taken from the total population with the Total Sampling technique, which was 137 people. Research samples were taken and met the inclusion criteria and exclusion criteria. The type of data collected is primary and secondary data. Data analysis used univariate and bivariate analysis with the contigency coefficient test at a significance level of 0.05. And the results of the analysis using the chy-square test statistics by assessing the relationship between the motivation of women of childbearing age in VIA screening showed an Asymp.sign value of 0.00, because the p-value of 0.00 <0.05, it can be concluded that there is a relationship between knowledge and motivation of women of childbearing age by performing VIA screening. It is expected that health workers can conduct health counseling and provide support to women of childbearing age in the working area of the rawamerta health center in order to increase the motivation for VIA screening.